2015
DOI: 10.1371/journal.pone.0134635
|View full text |Cite
|
Sign up to set email alerts
|

Iron Stores, Hepcidin, and Aortic Stiffness in Individuals with Hypertension

Abstract: Background & AimsIron accumulation within the arterial wall has been hypothesized to promote atherosclerosis progression. Aim of this study was to evaluate whether the hormone hepcidin and iron stores are associated with arterial stiffness in subjects with essential hypertension.MethodsCirculating hepcidin, ferritin, and mutations in the hemochromatosis gene were compared between subjects included in the first vs. third tertile (n=284 each) of carotid-femoral pulse wave velocity (PWV) in an unselected cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
(52 reference statements)
2
26
1
Order By: Relevance
“…15 Few studies have examined the relationship between serum ferritin level and arterial stiffness, and results have been inconsistent. 16,17 Therefore, we investigated the relationship between serum ferritin level and arterial stiffness in healthy Korean adults.…”
Section: Introductionmentioning
confidence: 99%
“…15 Few studies have examined the relationship between serum ferritin level and arterial stiffness, and results have been inconsistent. 16,17 Therefore, we investigated the relationship between serum ferritin level and arterial stiffness in healthy Korean adults.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, persistently high serum ferritin levels despite lifestyle changes correlate with hepatic and body iron (2,(9)(10)(11)(12). Most importantly, presence of DIOS is associated with more severe insulin resistance and evo-lution to type 2 diabetes, with hepatic and cardiovascular damage, and with hepatocellular carcinoma development (11,(13)(14)(15)(16)(17)(18). Viceversa, iron depletion by phlebotomy improved insulin resistance and liver damage (9,(19)(20)(21)(22)(23), suggesting that excess body iron is involved in the pathogenesis of metabolic disease (24,25).…”
mentioning
confidence: 99%
“…Clinical studies have shown increased PWV in iron‐overloaded patients due to β‐thalassaemia major (Detchaporn et al, ; Gedikli et al, ; Ulger, Aydinok, Gurses, Levent, & Ozyurek, ) or haemochromatosis (Cash et al, ). Furthermore, Valenti et al () identified an association between hyperferritinemia and aortic stiffness in hypertensive subjects, and Merchant et al () described that arterial stiffness increased significantly as cardiac iron‐overload increased in β‐thalassaemia patients receiving regular blood transfusions. On the other hand, Stakos et al () described that, in the absence of cardiac iron‐overload, patients with β‐thalassaemia major demonstrated aortic stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented by experimental and clinical studies that increased oxidative stress plays a key role in the cardiomyopathy following iron‐overloading (Bartfay & Bartfay, ; Cheng & Lian, ), and, although the relationship between iron deposit and cardiovascular damage has been known since the 1960s, iron‐overload vasculopathy has been poorly studied. Only a few clinical studies have suggested a relationship between iron stores and changes in BP (Cash et al, ), endothelial dysfunction (Gaenzer et al, ; Kukongviriyapan et al, ), and arterial stiffness (Cheung, Chan, & Ha, ; Detchaporn et al, ; Gedikli et al, ; Valenti et al, ). However, because these clinical studies have been based on patients of different ages, uncontrolled comorbidities, different iron levels, and diverse aetiology leading to iron‐overload (i.e., haemochromatosis, β‐thalassaemia, and sickle cell disease), the effects of chronic iron‐overload per se on vascular structure and function still remain under investigation.…”
Section: Introductionmentioning
confidence: 99%